Objectives and Program of the English Edition of the Journal of "Urban People" - Soukupová, Blanka (Lidé města, 2007)
The French anthropologist Marc Augé presented the city (large or small) as one of the three key problems (in his terminology, one of the three new “worlds”) of contemporary (postmodern) anthropology. However, whether we call the world a new “field” or, as it is usually called in Czech ethnology, an “organism,” this comparison will always contain a certain uniqueness, but, at the same time, mutual dependency and isolation from other worlds or organisms. The city represents a socially attractive, scientifically open topic.